Primary pericardial mesothelioma presenting as pericardial constriction: a case report. Issue 1 (15th December 2003) - Suman, S; Schofield, P; Large, S
Abstract : A 19 year old man presented with a six month history of chest pain, dyspnoea, and lethargy and was found on an echocardiogram to have a dilated left ventricle with a small pericardial effusion. Ramipril and a course of steroids were tried but serial echocardiograms showed a persistently thickened pericardium and slowly developing features of constriction. On computed tomography, a large mediastinal mass encasing the heart, along with para-aortic and paratracheal lymphadenopathy, was found. Right heart catheter studies showed equal pressures in all four chambers. His deteriorating clinical condition led to a pericardiectomy. Histology confirmed primary pericardial mesothelioma. The patient died soon after surgery.